Queer Indigenous Entropy: Sexual Circulation and the Conquest Narrative. (September 2014) - Gilley, Brian Joseph
Abstract Two‐Spirit men's sexual conquest stories—or what I am calling sexual coup stories—narrated more than just the sexual encounter. In fact, actual sexual acts are often secondary to the circumstances producing the sexual encounter. In this study, coup stories serve as a form of data revealing the ways in which sexual conquest is a sociosexual practice thoroughly embedded in broader Native community values and cultural patterns for the movement of bodily desire across landscapes predating humanist intellectual and moral intervention. Thus, the intra‐acting agencies of Native sexual circulation provide the opportunity to enact a culturally specific form of material‐discursive order that when viewed from the epistemological metropole look highly entropic (chaotic). Yet, Native sexual ontology realizes itself in the phenomena of a sexual circulation whose material‐discursive practices appear to be disordered from the highly ordered humanistic center.